A debreceni Kossuth Lajos Tudományegyetem archontológiája 1950-1990. III. rész - Mudrák, József (Gerundium, 2015)
THE ARCHONTOLOGY OF THE KOSSUTH UNIVERSITY III.: INSTITUTE OF HUNGARIAN LITERATURE AND LINGUISTICS (1950–1990). he archontology of the Faculty of Arts, the Faculty of Natural Scienences, and of the so called central units of the University of Debrecen between January 1, 1950 – December 31, 1990 was written based on the personal data from the Rector’s Oice supplemented by the documents of the Department of Administration concerning the less documented 50s. he existing documentation is not full, therefore the archontolgy cannot really be compiled with a 100% accuracy. he third part provided the complete list of the teachers and staf of the Institute of Hungarian Literature and Linguistics including everybody from Head of the Institute to the oice administratiors.